2017
DOI: 10.1177/0363546517692551
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Correction in Sleep Disturbance Is Sustained After Arthroscopic Rotator Cuff Repair

Abstract: At greater than 24 months, 41% of patients still demonstrated sleep disturbance, with both SST and VAS scores showing improvement. The prolonged use of narcotic medication negatively affects sleep, with a greater effect seen over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
2
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(106 citation statements)
references
References 9 publications
3
88
2
13
Order By: Relevance
“…The search strategy yielded 78 articles. After duplicate removal and titles, abstracts and full-texts review, four studies [1,2,14,19] were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy yielded 78 articles. After duplicate removal and titles, abstracts and full-texts review, four studies [1,2,14,19] were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep disturbance is one of the most common complains of patients with RC disease [1,3], with only 11% of patients with symptomatic RC tears claiming to have a normal sleep [1,14]. Patients with RC tears seems to have more sleep disturbances compared with patients with other shoulder disorders like RC tendinopathies [3], or subacromial impingement [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was surprising, as narcotic use has been associated with disruption of the sleep cycle. 6,13 Additionally, after evaluating sleep quality for a minimum of 2 years in 37 patients who underwent rotator cuff repair, Horneff et al 8 found that continued postoperative narcotic use was associated with decreased sleep quality. Given this information, we had hypothesized that narcotic use would have a negative impact on the change in sleep quality following rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%
“…Ağrı skoru arttıkça uyku kalitesinin bozulduğu bildirilmiştir. SSS'li hastalarda, gece agȓısı düzeyinin yüksek oldugȗ ve dizabilitede etkili oldugȗ gösterilmiştir [25][26][27][28]. Çalışmamızda, tüm hastaların uyku kalitesi kötüydü, gece ağrısı olan hastaların ileri düzeyde omuz dizabilitelerinin olduğu bulundu.…”
unclassified